Exploration of Erdaohe Silver Polymetallic Deposit in Inner Mongolia based on Induced Polarization Method - Baoyou Li; Zhiqing Shi; Zhiguang Yang; Lan Xu; Hanlie Cheng; David Sturdivant (Journal of Chemistry)
The exploration of Erdaohe Cu-Ag-Pb-Zn deposit in Zhalantun City, Inner Mongolia has entered the stage of blind exploration. It is a difficult problem at this stage whether common geophysical methods can find anomalies caused by 300∼1000 m or deeper Pb-Zn deposits in this area. Whether the problem is solved or not has a strong practical significance for the current and future prospecting work in this area. According to the theory of induced polarization sounding in time domain, it is considered in this paper that when the parameters such as high power, suitable device, and time delay are well coupled with the deep blind ore, it is possible to find anomalies caused by deep lead-zinc ore larger than 300 m. In order to prove the feasibility of the deep application of this method, the high-power induced polarization sounding experiment with different devices and different power supply cycles was carried out in Erdaohe copper-silver lead-zinc mine. The test results show that by adopting the measurement method of the encrypted equipotential device and selecting the appropriate polar distance, when the power supply period is 32 s, the time delay is 200 s and the sampling width is 200 s, a good deep lead-zinc mine anomaly can be found. The equipotential symmetrical quadrupole sounding MN/AB = 1/10 and the depth correction coefficient is 0.41 for inversion can accurately determine the anomaly location, which is worthy of popularization and application in this area. The ore bodies in this area are controlled by structures and distributed in lenticular layers along the fault footwall interlayer fracture zone. The ore bodies may change with the occurrence of the fracture surface. The characteristics of low resistivity, low slow, and high polarization of IP and single peak anomaly of IP sounding are important signs of lead-zinc prospecting in this area.